Features of the Reverse Stock Split of Joint Stock Companies-Banks - Avetisyan , V. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The author discussed the imperfect regulation of the institute of reverse stock split in the legislation of RA, the absence of clear differentiation line between interests of the main shareholders and the company, as well as the issues of application of foreign legislation in RA, without taking into consideration national peculiarities. The abovementioned issues compose a situation, where main shareholders of jointstock companies- banks, without any justification, at the expense of financial funds of the company and dividends of stockholders can get rid of small shareholders, take possession of their dividends and carry out the practice of centralization of the capital between several persons, without any prohibition. Any mechanism, which is directed to compose the controlling block of shares (including consolidation of safety stocks) as a rule has the aim to increase the effectiveness of management and activities of joint-stock company. However, the consolidation of safety stocks must be done in a way that can ensure not only carrying out the abovementioned goals, but also can provide protection of small shareholders' interests without any abuse of the powers given. Taking into consideration the necessity to balance the interests of joint-stock companies-banks and their stockholders, the author suggests several amendments in "Law on Joint-stock companies" and "Law on Banks and Banking", which will allow finding solution to the abovementioned issue.
Keywords: bank, reverse stock split, fractional shares, redemption of shares, the main shareholder, minority shareholder, protection of shareholders' rights